Dari Ide ke Realitas: Langkah-Langkah untuk Memulai Usaha Baru (Inovasi) - Melisusantibeli Melisusantibeli; Dedi Dedi; Yosia Belo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This paper explores the significance of innovation in starting a new business, especially in the midst of the rapid changes of the digital era. In an increasingly competitive atmosphere, innovation has become a necessity for entrepreneurs to maintain their relevance and competitiveness. The study classifies the different types of innovation—including products, processes, and business models—as well as the strategies that can be implemented to stimulate innovation in organizations. In addition, this article also examines the challenges that arise in the application of innovation, such as dissatisfaction with change, limited resources, and the need to master new skills. By raising case studies of entrepreneurs who have succeeded through innovation, this paper illustrates how creative approaches can open up new opportunities and have a positive impact on society. Through a deeper understanding of innovation, businesses can overcome challenges and find effective strategies to succeed in an ever-changing market.